ANALISA PERKEMBANGAN UMKM DI INDONESIA PADA TAHUN 2017 - 2019 - TEGUH SANTOSA; YENIASARI RIZKIA BUDI (Institut Bisnis Muhammadiyah Bekasi, 2020)
The development of economic growth is certainly supported by the increasing volume of goods and services that can provide prosperity for the community. Economic development can be seen from the increase in GDP regardless of whether the increase is smaller or larger than population growth. Micro, small and medium enterprises (UMKM) are one of the business units that have an important role in the development and growth of the country's economy. UMKM business growth is certainly an opportunity as a field to find work and income, with a lot of employment in UMKM showing that UMKM has a strategic role for the government in helping to reduce poverty and unemployment. The MSME sector has a large share of the Indonesian economy. Based on information obtained from the Ministry of Cooperatives and UMKM, in 2019 UMKM had a proportion of 99.9% of the total number of more than 65 million registered business units. The proportion of loans given to UMKM has always increased from 2017 to 2019 in accordance with the size of the business established. The largest contribution to PDB is provided by the micro-enterprise sector. The micro-enterprise sector annually contributes more than 25% to PDB compared to other sectors which are only able to contribute below 20%